Diversification of Making Chicken Meatballs with Sweet Potato Substitution (Ipomoea batatas L) by Different Concentrations - Ika Rezvani Aprita; Irhami Irhami; Chairil Anwar; Reza Salima (Department of Animal Sciences, Faculty of Agriculture, Sriwijaya University, Indonesia, 2020)
ABSTRACTMeatballs are food products in the form of spheres obtained from a mixture of livestock meat (meat content not less than 50% of the total mixture) with the process of meat grinding, doung making, meatballs making and meatballs printing. The purpose of this study was to determine how the effect yellow sweet potato addition improved the quality of meatballs chicken. This study used a Completely Randomized Design (CRD) with three levels of yellow sweet potato 65, 75 and 85% and six replications. The results showed that the addition of yellow sweet potato significantly influenced the value of beta-carotene and flavor. Meatballs with the addition of 65% yellow sweet potato based on organoleptic test obtained the best quality based on color ie 3.25 (acceptance level rather like), taste 3.43 (acceptance level rather like), texture 3.20 (acceptance level rather like) and at the concentration of 75% obtained the best quality only at the aroma that is 3.2 (acceptance level rather like).